Rancang Bangun Sistem Informasi Pengelolaan Surat Pada Kelurahan Tonja Berbasis Web - Teny Indrayani (JATISI, 2025)
Tonja Village currently manages administrative correspondence, including incoming and outgoing letters, manually. As a result, the processes of recording, letter disposition, and archiving are inefficient. Retrieving old archives becomes difficult, and documentation for reporting is not properly recorded. To address these issues, SISMARAJA was developed as a digital solution for managing incoming and outgoing correspondence. The system has been tested using usability testing methods and has proven to facilitate faster and more organized processes of disposition, recording, and document archiving. This research employs a qualitative method and adopts the waterfall development model. The system was built using the Bootstrap framework. With SISMARAJA, public services in Tonja Village are expected to become more effective and transparent.